I this the answer you are looking for would probably be 47.7%.
hope this helps!!
Question..
Combine like terms to create an equivalent expression.
½ −⅙q +⅚q - ⅓
Answer:
½ −⅙q +⅚q - ⅓ is equivalent to ⅔q + ⅙
Step-by-step explanation:
Given
½ −⅙q +⅚q - ⅓
Required
Equivalence
½ −⅙q +⅚q - ⅓
We start by collecting like terms.
⅚q - ⅙q + ½ - ⅓
Factorize
(⅚ - ⅙)q + ½ - ⅓
((5 - 1)/6)q + ½ - ⅓
(4/6)q + ½ - ⅓
Reduce 4/6 to lowest term
⅔q + ½ - ⅓
Evaluate fraction
⅔q + (3 - 2)/6
⅔q + ⅙
Hence, ½ −⅙q +⅚q - ⅓ is equivalent to ⅔q + ⅙
Answer:
B
Step-by-step explanation:
600+125+175=900-400(deposit)=500
or
600-125-175-300-200=100+400=500
Brainliest Please :)
First error is that the legs are a and b so a should be x and b is 6 and c is 10 the second error is at the end they did not take the square root to get x by itself the real answer should be
X^2 +6^2=10^2
X^2+36=100
X^2 =64
X=8
Answer:
15 to 21
Step-by-step explanation:
junk to total